Pengembangan Aplikasi My Home Menggunakan Metode Prototype - Hartini Ramli; A. Alfatira Nur Aisah; Muhammad Nuralamsyah; Alif Kurniawan (Sakura Digital Nusantara, 2023)
Tourism is a branch of the economy which is one of the pillars of the economy in many countries in the world, including in Indonesia. The many tourist attractions in Indonesia, the more lodging services that become a stopover for tourists or travellers. My Home is the right solution for people who need lodging such as apartments, villas and townhouses. This application displays general information such as addresses, pictures, owner contacts and prices for lodging. This research uses the Prototype method which is designed using various diagrams, such as activity diagrams, class diagrams, sequence diagrams, and use cases to facilitate the design and design. By using the My Home application, customers can easily search for and book lodging without the need to physically visit the place. Thus, My Home becomes a solution that helps users find lodging that matches customer preferences, speeds up the reservation process, and provides comfort and convenience. convenience in the customer journey.